Nanomaterials and Nanofabrication for Electrochemical Energy Storage - Liu, Jian; Lu, Dongping; Wang, Xiaolei; Liu, Jian; Lu, Dongping; Wang, Xiaolei (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Electrochemical energy storage technologies play key roles for storing electricity harvested from renewable energy resources of an intermittent nature, such as solar and wind, and for utilizing electricity for a range of applications, such as electric vehicles and flights, wearable electronics, and medical implants. This book collects original research work on the fabrication of various nanomaterials, their applications in battery and supercapacitor technologies, and the investigation of the underlying structure-property-performance correlation in these complex energy systems.
English
Keywords: Technology: general issues